Waqf Edumedia: Social Media as a Means of Developing Waqf Literacy in Indonesia - Hakiki, Muhamad Fuji; Asrofi, Mohammad; Julendra, Alif Khuwarazmi Maulana (Journal of Islamic Economic Scholar, 2020)
Waqf is one of the financing instruments in Islam. Along with the times, waqf is transformed not only consumptive but also productive. The potential for waqf in Indonesia in 2019 is based on data from the Indonesian Waqf Board or BWI of 300 Trillion per year, but this has not been realized by the general public. In reality, this potential cannot be optimally realized, one of which is due to the low level of literacy in public knowledge about waqf. The purpose of this research is to find out and empirically test how social media can increase the level of community literacy about waqf. The method used in this research is quantitative with Technology Acceptance Models (TAM) which is processed through structural equation modeling (SEM). Collecting data in the field using a survey method with a questionnaire instrument. This research is expected to be able to contribute to the development of waqf literacy so that it can optimize the potential of waqf.Keywords : Waqf, Waqf Edumedia, Social Media, TAM